Career Women In Achieving Samawa Family In The Post-Truth Era Islamic Legal Perspective - Syaibani, Syaibani (MAQASID, 2023)
Islamic history records that women have a meaningful role in various metamorphosis of society, customs, commerce and politics in the country. Gender balance is a social issue and is often a contentious topic. People assume that gender dimilarity can cause various forms of inequality, such as the unimportance of roles related to political policies, women are only in the three R's, namely kitchen, well, mattress. Injustice was hated by Allah. Almighty, he had put Adam and Eve in a dignified position. Islamic law provides solutions in solving family problems that occur. However, sometimes, existing laws cannot be understood regarding wisdom and philosophy, resulting in the assumption of Islamic law that is no longer representative in resolving Islamic family civil cases. The problems that occur in the post-truth era of women are often blamed for being career women. Even though there are some women who are able to break through thick walls and are able to have a career outside the home. This career did not prevent her from carrying out her duties, rights and obligations as a wife. But there are so many assumptions that by being a woman, family careers are not taken care of and families are not achieved.